Pendekatan Cognitive Behavioral Therapy Untuk Mereduksi Trauma Korban Bencana Alam - Salsabila Arsih; Netrwawati; Yeni Karneli (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
Indonesia is geographically, geologically, and demographically prone to natural disasters. This results in a frightening and psychologically shaking life for victims of natural disasters in the form of stress and trauma experienced. If not handled properly, this condition becomes a serious threat to life after natural disasters. they need counseling services to reduce trauma and stabilize their emotions. This research aims to help reduce the trauma of victims of natural disasters and return to a healthy psychological condition. The research method used is literature study, collecting data by constructing various sources such as books, journals, and research. Cognitive Behavioral Therapy (CBT) is provided in the form of counseling service assistance, chosen to change the cognitive and behavior of victims that cause traumatic conditions.